ALARM NMR for HTS Triage and Chemical Probe Validation. Issue 1 (9th April 2018) - Dahlin, Jayme L.; Cuellar, Matthew; Singh, Gurpreet; Nelson, Kathryn M.; Strasser, Jessica M.; Rappe, Todd; Xia, Youlin; Veglia, Gianluigi; Walters, Michael A.
Abstract: Nonspecific target engagement by test compounds and purported chemical probes is a significant source of assay interference and promiscuous bioactivity in high‐throughput screening (HTS) and chemical biology. Most counter‐screens for thiol‐reactive compounds utilize mass spectrometry or fluorescence detection, as well as nonproteinaceous reporters like glutathione that may not always approximate the reactivity of protein side chains. By contrast, a L a a ssay to detect r eactive m olecules by n uclear m agnetic r esonance (ALARM NMR) is an industry‐developed protein‐based [ 1 H‐ 13 C]‐heteronuclear multiple quantum coherence NMR counter‐screen to identify nonspecific protein interactions by test compounds by reporting their tendencies to modulate the human La antigen conformation. This article is a user's guide to the production of the 13 C‐labeled La antigen reporter protein and reaction of test compounds with this reporter protein, as well as the collection and analysis of characteristic NMR spectra. Combined with other assay interference counter‐screens, this assay will enhance chemical biology by helping researchers better prioritize chemical matter, which will increase the number of tractable HTS screening actives and aid in the development of better chemical probes. © 2018 by John Wiley & Sons, Inc.